2013
DOI: 10.1073/pnas.1212346110
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen trifluoride global emissions estimated from updated atmospheric measurements

Abstract: Nitrogen trifluoride (NF 3 ) has potential to make a growing contribution to the Earth’s radiative budget; however, our understanding of its atmospheric burden and emission rates has been limited. Based on a revision of our previous calibration and using an expanded set of atmospheric measurements together with an atmospheric model and inverse method, we estimate that the global emissions of NF 3 in 2011 were 1.18 ± 0.21 Gg⋅y −1 , or ∼20 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Compounds added only recently to routine Medusa measurements (and therefore not yet in Table 1) are HCFC-133a and CF 3 CFOCF 2 , while the light hydrocarbons C 2 H 2 and C 2 H 4 , although still measured, are also not included in Table 1 because co-elution compromises their measurement as the GC column ages. The AGAGE Medusas were the first instruments monitoring in situ the global distributions and trends of the high-GWP industrial gases CF 4 , NF 3 , and SO 2 F 2 Weiss et al, 2008;Arnold et al, 2013). In addition to the compounds listed in Table 1, additional species (e.g., CFC-112) are in various stages of being added to the station measurements.…”
Section: Medusa Gc-ms Instrumentsmentioning
confidence: 99%
“…Compounds added only recently to routine Medusa measurements (and therefore not yet in Table 1) are HCFC-133a and CF 3 CFOCF 2 , while the light hydrocarbons C 2 H 2 and C 2 H 4 , although still measured, are also not included in Table 1 because co-elution compromises their measurement as the GC column ages. The AGAGE Medusas were the first instruments monitoring in situ the global distributions and trends of the high-GWP industrial gases CF 4 , NF 3 , and SO 2 F 2 Weiss et al, 2008;Arnold et al, 2013). In addition to the compounds listed in Table 1, additional species (e.g., CFC-112) are in various stages of being added to the station measurements.…”
Section: Medusa Gc-ms Instrumentsmentioning
confidence: 99%
“…The present-day mixing ratio will therefore be close to 1 ppt, assuming no change in emission rate. Arnold et al (2013) found undetectable levels of NF 3 prior to 1975 in archived air samples and ice cores, indicating that the major source of the gas is anthropogenic.…”
Section: Introductionmentioning
confidence: 99%
“…NF 3 is being used increasingly as a replacement for banned perfluorocarbons (PFCs) which were utilised in processes such as chemical cleaning and circuit etching. It is an extremely potent greenhouse gas with an estimated 100-year global warming potential (GWP) between 10 800 and 17 000 (Arnold et al, 2013;Robson et al, 2006;Weiss et al, 2008). Weiss et al (2008) reported a 2008 mean global tropospheric mixing ratio of 0.45 ppt increasing at a rate of 0.053 ppt yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…According to an expanded set of atmospheric measurements [5], the global atmospheric abundance of NF 3 continues to rise; the mean concentration in the global background troposphere was 0.86 ± 0.04 ppt during mid-2011 [1]. On the AGAGE (Advanced Global Atmospheric Gases Experiment) website (http://agage.mit.edu/), the global mean concentration of NF 3 was 1.236 ± 0.058 ppt in February 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen trifluoride (NF 3 ) has the potential to make a growing contribution to the Earth's radiative budget [1]. The use of NF 3 has increased rapidly as a replacement for perfluorocarbons (PFCs) and SF 6 in industrial processes [2].…”
Section: Introductionmentioning
confidence: 99%